INTERACTIVE AND EDUCATIVE LEARNING MEDIA IN ENGLISH LANGUAGE TEACHING AT SENIOR HIGH SCHOOLS - Sitti Hadijah; Marhamah Marhamah; Shalawati Shalawati (AL-ISHLAH: Jurnal Pendidikan, 2020)
This research aims to describe senior high school students’ perspectives about the use of learning media in English language teaching context and to investigate the sorts of interactive and educative learning media in English language teaching. This research worked on descriptive research design, both qualitative and quantitative data were collected through a questionnaire. This study involved 171 senior high school students who voluntary filled in the questionnaire. The research findings reveal that the use of learning media to support learning process needs to be improved since the media used needs to be adjusted with the current trend of learning that is technology-based learning media. In addition, Powerpoint slides, video, film, online or traditional games were found as interactive and educative learning media from the students’ perspectives. The students are excited when the teachers are presenting media in their learning process, even though it only simply presented through Powerpoint. In other words, learning media has an essential role to support effective learning atmosphere for the students.